An omission in guidelines. Cardiovascular disease prevention should also focus on dietary policies for healthcare facilities. Issue 1 (January 2023) - de Frel, Daan L.; Assendelft, Willem J.J.; Hondmann, Sara; Janssen, Veronica R.; Molema, Johanna J.W.; Trines, Serge A.; de Vries, Iris A.C.; Schalij, Martin J.; Atsma, Douwe E.
Summary: Suboptimal diet is a major modifiable risk factor in cardiovascular disease. Governments, individuals, educational institutes, healthcare facilities and the industry all share the responsibility to improve dietary habits. Healthcare facilities in particular present a unique opportunity to convey the importance of healthy nutrition to patients, visitors and staff. Guidelines on cardiovascular disease do include policy suggestions for population-based approaches to diet in a broad list of settings. Regrettably, healthcare facilities are not explicitly included in this list. The authors propose to explicitly include healthcare facilities as a setting for policy suggestions in the current and future ESC Guidelines for cardiovascular disease prevention in clinical practice.